2012
DOI: 10.1073/pnas.1203005109
|View full text |Cite
|
Sign up to set email alerts
|

Rethinking dog domestication by integrating genetics, archeology, and biogeography

Abstract: The dog was the first domesticated animal but it remains uncertain when the domestication process began and whether it occurred just once or multiple times across the Northern Hemisphere. To ascertain the value of modern genetic data to elucidate the origins of dog domestication, we analyzed 49,024 autosomal SNPs in 1,375 dogs (representing 35 breeds) and 19 wolves. After combining our data with previously published data, we contrasted the genetic signatures of 121 breeds with a worldwide archeological assessm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
337
0
13

Year Published

2015
2015
2018
2018

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 455 publications
(361 citation statements)
references
References 38 publications
11
337
0
13
Order By: Relevance
“…This is because archaeological research has indicated dingoes probably represent the earliest translocation of canids across ISEA and introduction to the Australasian region. This interpretation is supported by the genetic evidence, which places these relatively ancient dog breeds at the base of phylogenetic trees (Larson et al 2012). Salvolainen et al (2004) analysed modern mtDNA from 211 dingoes, 38 Eurasian wolves and 676 dogs from all continents, as well as 19 pre-European archaeological dog samples from Polynesia.…”
Section: Dogssupporting
confidence: 60%
“…This is because archaeological research has indicated dingoes probably represent the earliest translocation of canids across ISEA and introduction to the Australasian region. This interpretation is supported by the genetic evidence, which places these relatively ancient dog breeds at the base of phylogenetic trees (Larson et al 2012). Salvolainen et al (2004) analysed modern mtDNA from 211 dingoes, 38 Eurasian wolves and 676 dogs from all continents, as well as 19 pre-European archaeological dog samples from Polynesia.…”
Section: Dogssupporting
confidence: 60%
“…Novas pesquisas mostram que os cães atuais não descendem do lobo cinzento (como se acreditava até muito recentemente), mas sim de um lobo desconhecido e extinto, e também que a domesticação ocorreu enquanto humanos eram caçadores e coletores (Freedman et al, 2014;Larson, 2012). A novidade é que não foram os humanos que domesticaram os cães-lobos, mas estes últimos que se aproximaram dos humanos por conta própria, identificando-os como um novo nicho ecológico que podiam explorar (Larson, 2012). 4…”
Section: Introductionunclassified
“…It is generally accepted on the basis of archaeological and genetic findings that the timing of dog domestication dates from 15,000-16,000 BP (Late Upper Palaeolitic) in East Asia (Larson et al, 2012;Perri, 2016). However, a recent molecular study (Skoglund et al, 2015) used genome sequencing of a 35,000 year old Siberian wolf to suggest that the ancestors of dogs were separated from present-day gray wolves before the Last Glacial Maximum.…”
Section: Body Size and Sexual Size Dimorphism Of Domestic Dogs And Catsmentioning
confidence: 99%